Utilization of Melinjo Skin Waste into Flakes and Stock: Training and Evaluation of Product Acceptance in Karangtawang Village, Kuningan, West Java - Farhan Ilham Wira Rohmat; Mohammad Fitra Chefario; Natasya Nurhaliza; Deswita Kartika Putri; Krisna Aldi Nugraha; Yatti Sugiarti; Sri Handayani; Dewi Nur Azizah; Nita Nur Rezkia; Maulana Noor Fajri Al Hajar (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aims to address the issue of melinjo peel and leaf waste in Karangtawang Village, Kuningan Regency, through the application of zero waste food processing technology. The target partner for this activity is the Mujursari Farmer Group. The implementation methods include surveys, counseling, technical training on product manufacturing, and mentoring. The products developed are based on optimization research for broth formulations based on melinjo waste (peels and leaves) as well as gnemon flakes. The results indicate effective technology transfer, where the community is capable of producing broth variants with the best formulation (90% melinjo peel : 10% leaves) which received high sensory acceptance. This program is expected to increase the economic value of the waste by up to IDR 15-20 million per month and support sustainable agriculture.